Unveiling the Proton‐Feeding Effect in Sulfur‐Doped Fe−N−C Single‐Atom Catalyst for Enhanced CO2 Electroreduction - Chen, Shanyong; Li, Xiaoqing; Kao, Cheng‐Wei; Luo, Tao; Chen, Kejun; Fu, Junwei; Ma, Chao; Li, Hongmei; Li, Ming; Chan, Ting‐Shan; Liu, Min (Angewandte Chemie International Edition, 2022)
Heteroatom‐doping in metal‐nitrogen‐carbon single‐atom catalysts (SACs) is considered a powerful strategy to promote the electrocatalytic CO2 reduction reaction (CO2RR), but the origin of enhanced catalytic activity is still elusive. Here, we disclose that sulfur doping induces an obvious proton‐feeding effect for CO2RR. The model SAC catalyst with sulfur doping in the second‐shell of FeN4 (Fe1−NSC) was verified by X‐ray absorption spectroscopy and aberration‐corrected scanning transmission electron microscopy. Fe1−NSC exhibits superior CO2RR performance compared to sulfur‐free FeN4 and most reported Fe‐based SACs, with a maximum CO Faradaic efficiency of 98.6 % and turnover frequency of 1197 h−1. Kinetic analysis and in situ characterizations confirm that sulfur doping accelerates H2O activation and feeds sufficient protons for promoting CO2 conversion to *COOH, which is also corroborated by the theoretical results. This work deepens the understanding of the CO2RR mechanism based on SAC catalysts. Sulfur‐doping in the second coordination shell of FeN4 induces the increased CO2 reduction reaction (CO2RR) performance relative to pristine FeN4. The proton‐feeding effect after sulfur doping is demonstrated to promote protonation of *CO2 to *COOH, and thus CO2RR performances, through kinetic analysis, in situ characterization and DFT calculations.